Pendidikan Tata Cara Pelaksanaan Haji dan Umrah Bagi Mahasiswa PGMI Pada Mata Kuliah Fiqih Ibadah - Muhammad Fadhly; Muhammad Alif Al Aziz; Azzahra Kamila Cahyani Masdar; Lailatun Nadira; Wismanto Wismanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The word Hajj comes from Arabic and has a linguistic meaning. In language, Hajj means intentionally, in the Sharia Hajj means deliberately visiting the Kaaba to carry out worship which includes tawaf, sa'i, wuquf and other acts of worship. Other offerings aim to fulfill Allah SWT's commands and hope in Him. Umrah literally means